OVERVIEW OF PROCESSING INSTALLATIONS FOR MINERAL AGGREGATES - Cătălina IANĂȘI; Nicoleta Maria MIHUȚ (Fiabilitate şi Durabilitate)
The problems faced by economic societies today represent real challenges that require comprehensive solutions. The raw materials must be used rationally and the production processes and work technologies, within these processes, must not harm the environment. Another problem is the lack of appropriately qualified labor in certain economic fields. These represent only part of the problems that most companies face, problems that they must manage to overcome for a profitable and sustainable economic development.